Optimalisasi Usaha Minuman Teh Kekinian di Bestea Semarang, Desa Karangtempel, Kecamatan Semarang Timur, Kota Semarang - Meddiati Fajri Putri; Juwita Ria Rumondang; Moch Faizal Rachmadi; Arina Haque; Thamrin Thamrin; Zaimatun Nabilah; Sultan Ahmad El Hakim (LPPM Politeknik Piksi Ganesha, 2025)
Tea drinks have become an integral part of everyday life for Indonesians, especially in large cities. The development of the beverage industry has led to product diversification, encompassing a variety of traditional and modern tea variants, such as bubble tea and milk tea, catering to diverse consumer tastes. Globalization and modernization have also played a significant role in increasing the accessibility and variety of tea drinks in Indonesia, while innovative marketing and smart promotions have boosted the popularity and market penetration of contemporary tea beverage businesses like BesTea Semarang. However, it is crucial for businesses to maintain product quality, hygiene, and service to maintain and improve customer satisfaction and competitiveness in an increasingly competitive market. Contemporary tea beverage businesses like BesTea Semarang face numerous challenges. The main challenges are bee infestations due to the use of refined sugar in production, as well as declining sales during unfavorable weather conditions. Furthermore, there are issues with waste management and a lack of employee knowledge about customer service. As a solution, the community service team provides training and mentoring on the production of healthy herbal tea beverages, natural methods for repelling bees, and improving customer service. The results of the community service activities demonstrated improved product quality through diversification of herbal teas based on peppermint and spices, as well as enhanced human resource capacity in customer service. The implementation of this solution successfully increased sales and customer satisfaction at BesTea Semarang.